Validation of a Portuguese version of the Information Needs in Cardiac Rehabilitation (INCR) scale in Brazil - Ghisi G.L.D.M. (2014)
Objectives: To translate, culturally adapt and psychometrically validate the Information Needs in Cardiac Rehabilitation (INCR) tool to Portuguese. Background: The identification of information needs is considered the first step to improve knowledge that ultimately could improve health outcomes. Methods: The Portuguese version generated was tested in 300 cardiac rehabilitation patients (CR) (34% women; mean age=61.3±2.1 years old). Test-retest reliability was assessed using intraclass correlation coefficient (ICC), the internal consistency using Cronbach's alpha, and the criterion validity was assessed with regard to patients' education and duration in CR. Results: All 9 subscales were considered internally consistent (á>0.7). Significant differences between mean total needs and educational level (p<0.05) and duration in CR (p=0.03) supported criterion validity. The overall mean (4.6±0.4), as well as the means of the 9 subscales were high (emergency/safety was the greatest need). Conclusion: The Portuguese INCR was demonstrated to have sufficient reliability, consistency and validity. © 2014 Elsevier Inc.